Analisis Arus Balik Pada Hilir Sungai Bolango Menggunakan Metode Integrasi Numerik - Salsadilla, Namira; Husnan, Rawiyah; Labdul, Barry Yusuf (Jurnal Teknik Sumber Daya Air, 2025)
Rivers are graphic phenomena that form naturally where water flows continuously to lower areas. The downstream or estuary is the end of the river flow which leads to the sea, lake, ocean, or even to a larger river. High-intensity rainfall can lead to overflow because it increases the discharge of water flow in the river beyond the capacity. The overflows that occur downstream and turn upstream are called backflow. This study aimed to examine the occurrence of backflow in downstream of the Bolango River. The research utilized secondary data, such as rainfall and tidal data, and the Bolango-Bone watershed map. Those data were analyzed through hydrological method to obtain design of flood discharges that were collaborated with hydraulics analysis using the Numerical Integration Method to obtain the water level profiles. The results of the hydrological analysis obtained: the design of flood discharge using the Nakayasu Synthetic Unit Hydrograph Method for a 25-year return period was 2046,81 m3/second, a 50-year return period was 2135,72 m3/second, and a 100-year return period was 2209,06 m3/second, and each occurred at the 8th hour. The result of the hydraulics analysis disclosed that the downstream of the Bolango River belonged to the type of sloping surface flow profile or M (Mild) profile because the riverbed slope was smaller than the critical slope.